Exopolysaccharide and lactic acid bacteria: Perception, functionality and prospects - Vivek K. Bajpai; Irfan A. Rather; Rajib Majumder; Shruti Shukla; Abhinav Aeron; Kangmin Kim; Sun Chul Kang; R. C. Dubey; D. K. Maheshwari; Jeongheui Lim; Yong-Ha Park (Bangladesh Pharmacological Society, 2015)
Lactic acid bacteria exhibit the most effective potential to divert significant amount of fermentable sugars towards the biosynthesis of functional exopolysaccharide. Exopolysaccharides from lactic acid bacteria are receiving a renewed interest due to the claims of human health benefits. This review provides an update on multiple uses and production of exopolysaccharides with major emphasis on their chemical properties, characterization, and some other molecular strategies adopted for their genetics and biological tailoring to better understand the process of exopolysaccharide production along with their antiviral efficacy with multiple modes of action. Additionally, microbiological, biochemical, nutritional and biotechnological aspects of exopolysaccharide production have also been discussed. Moreover, appro-priate suggestions have been made on lactic acid bacteria improvements, leading to enhanced production with advanced modification and production process that may contribute to the economic soundness of applications in food and pharmacological industries with this promising group of biomolecules.